2010
DOI: 10.1007/s11119-010-9191-4
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of a laser rangefinder to characterize winter wheat

Abstract: In recent years, laser rangefinder sensors have been introduced to the practice and research of agricultural engineering. In research, laser rangefinders have been investigated in horticulture and agriculture. For vehicle-based determination of crop biomass, commercially available laser rangefinders have been analysed and tested to measure aboveground biomass in oilseed rape, winter rye, winter wheat, oats and grassland. Resulting from limited measuring range and fixed beam types, the laser rangefinder models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…They related either the vegetation volume or the reflection height (distance between crop surface and laser scanning unit) derived by triangulation or time-of-flight of the reflected laser beam with biomass and LAI measurements. The studies reported R 2 values for FBM between 0.77 and 0.99, for DBM between 0.72 and 0.99 and for LAI between 0.70 and 0.96 [22,54,55]. Sensing LAI was further investigated using a combined radiometer and ultra-sound sensing system yielding an R 2 value of 0.84 [24] and a mobile LAI system based on canopy light transmittance yielding R 2 values ranging from 0.73 to 0.86 [20] between the sensor and LAI reference measurements.…”
Section: Discussionmentioning
confidence: 99%
“…They related either the vegetation volume or the reflection height (distance between crop surface and laser scanning unit) derived by triangulation or time-of-flight of the reflected laser beam with biomass and LAI measurements. The studies reported R 2 values for FBM between 0.77 and 0.99, for DBM between 0.72 and 0.99 and for LAI between 0.70 and 0.96 [22,54,55]. Sensing LAI was further investigated using a combined radiometer and ultra-sound sensing system yielding an R 2 value of 0.84 [24] and a mobile LAI system based on canopy light transmittance yielding R 2 values ranging from 0.73 to 0.86 [20] between the sensor and LAI reference measurements.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In a previous study of plant height determination, Ehlert et al [13][14][15] proposed an approach of observing plant height in flat areas with a known ground level. The laser scanner is mounted on a tool carrier with an inclination angle (φ) to observe the plant from above.…”
Section: Introductionmentioning
confidence: 99%
“…The accumulation of biomass is central to agricultural productivity but the non-invasive monitoring of biomass using various sensors has thus far yielded only moderate prediction accuracies789. This may be attributed to the failure in combining information derived from different but complementary types of sensors10.…”
mentioning
confidence: 99%